Pengaruh Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian pada Mesin Cuci Merek LG di Kota Surabaya - Fauziah, Ike Nur; Supriyono, Supriyono (Universitas Batanghari, 2024)
The aim of the research is to analyze the effect of perceived quality and product price on purchasing decisions on LG brand washing machines in the city of Surabaya. The population in this study are washing machine buyers and users in the city of Surabaya. Determination of sampling in research using purposive sampling technique and the number of samples used is 104 respondents. The data used is primary data and data collection is done by distributing questionnaires to buyers and users of LG brand washing machines in the city of Surabaya. Then the analysis technique used is Partial Least Square (PLS). through the results of the study it is known that price perceptions and product quality contribute significantly to purchasing decisions on LG Brand Washing Machines in the City of Surabaya.